THE SEMANTICS OF ANTHROPOMORPHIC FIGURES AND SCENES IN THE BRONZE AGE PETROGLYPHS OF THE GREATER KARATAU RANGE (Journal of history, 2025)
This article explores images dated to the Bronze Age found among the petroglyphs of the Greater Karatau mountain range, which stretches from the southeast to the northwest through the territories of the Zhambyl, Turkistan, and Kyzylorda regions in southern Kazakhstan. The study focuses on analyzing the internal semantics of these images. Thanks to specialized and supplementary research conducted over the past 20+ years, thousands of materials have been collected and used to reassess and refine the chronological framework of the region’s rock art. Contrary to earlier studies that placed the Bronze Age depictions in the mid-2nd millennium BCE, current results suggest they should be dated from the end of the 3rd millennium BCE to the beginning of the 2nd millennium BCE. Among both individual figures and larger compositions typical of the Bronze Age, this study highlights images related to the universal “mother goddess” and “fertility cult” motifs, which are found across nearly all regions of the world. Originating in the Upper Paleolithic period, the image of the “mother goddess”—widely known as the "Paleolithic Venuses"—is noted for its highly universal nature. These figures are analyzed in relation to their material culture counterparts, as well as through parallels found in ethnographic, folkloric, and mythological texts. Various interpretations exist regarding the many roles of the “mother goddess” figure, including associations with “Earth Mother,” “Water Mother,” “forest or legend deity,” “agricultural deity,” “goddess of fertility and vegetation,” “protector of women in childbirth,” and “primordial mother,” among others.
Keywords: Karatau, Plot or Narrative, Anthropomorph or Anthropomorphic figure, Semantics, Archaeology, Bronze Age, Mother Earth, Mother Water or Water Mother (depending on context), Mythology.